Hello, puddle! - Sanchez, Anita, 1956- (Clarion Books, an imprint of HarperCollins Publishers, 2022)
"A nonfiction picture book exploring a deceptively simple but unexpectedly crucial resource for wildlife: puddles! This lyrical, gorgeously illustrated nonfiction picture book is perfect for young science learners and nature lovers. A normal everyday puddle may not seem very special. But for a mother turtle, it might be the perfect place to lay her eggs. For a squirrel, it might be the only spot to cool off and get a drink when the sun is shining down in July. And for any child, it can be a window into the elegant, complex natural world right outside their window. With lush, playful illustrations and fun facts about the animals featured, Hello, Puddle! is a joyful celebration of the remarkable in the ordinary, and the importance of even the most humble places in fostering life." --